2018
DOI: 10.1038/sdata.2018.72
|View full text |Cite
|
Sign up to set email alerts
|

The electronic Rothamsted Archive (e-RA), an online resource for data from the Rothamsted long-term experiments

Abstract: The electronic Rothamsted Archive, e-RA (www.era.rothamsted.ac.uk) provides a permanent managed database to both securely store and disseminate data from Rothamsted Research’s long-term field experiments (since 1843) and meteorological stations (since 1853). Both historical and contemporary data are made available via this online database which provides the scientific community with access to a unique continuous record of agricultural experiments and weather measured since the mid-19th century. Qualitative inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 58 publications
(39 reference statements)
2
21
0
Order By: Relevance
“…This could be explained by our assumptions about agronomic management practices that are effective in meeting the N demand and achieving full control of any weed, disease and pest infestations, factors that may reduce the national mean wheat yield. The mean baseline wheat yields in the present study are close to good year wheat yields (8–14 t ha -1 ) as reported by various studies across the UK and NZ ( Carmo-Silva et al, 2017 ; Craigie et al, 2015 ; Curtin et al, 2008 ; Perryman et al, 2018 ; Roques et al, 2017 ). Different studies reported similar yield potentials of current wheat cultivars under optimal managements in high productive countries at high latitude ( Boogaard et al, 2013 ; Schils et al, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…This could be explained by our assumptions about agronomic management practices that are effective in meeting the N demand and achieving full control of any weed, disease and pest infestations, factors that may reduce the national mean wheat yield. The mean baseline wheat yields in the present study are close to good year wheat yields (8–14 t ha -1 ) as reported by various studies across the UK and NZ ( Carmo-Silva et al, 2017 ; Craigie et al, 2015 ; Curtin et al, 2008 ; Perryman et al, 2018 ; Roques et al, 2017 ). Different studies reported similar yield potentials of current wheat cultivars under optimal managements in high productive countries at high latitude ( Boogaard et al, 2013 ; Schils et al, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…Originally conceived as an investigation into nutritional requirements for wheat growth, the continuous records, varied inputs and the modifications to crop management that have been put in place over the course of the experiment, coupled with a range of varieties grown, each for periods of several years, contribute to making this an exemplar long term G x E x M experiment. The experiment has been recently fully described and datasets are available electronically on request ( Johnston and Poulton, 2018 ; Perryman et al., 2018 ). Yields from 1852 to 2016 for selected treatments are shown in Figure 3 .…”
Section: Broadbalk As a Historic Exemplar G X E X M Experimentsmentioning
confidence: 99%
“…Long term trends in yield responses are clearly seen, and whilst year to year variation is observed, this is not apparent in the figure as the data is presented as multi-year means. Due to multiple factors included over time, these datasets represent a valuable resource for investigating G x E x M, and are all available on request ( Perryman et al., 2018 ).…”
Section: Broadbalk As a Historic Exemplar G X E X M Experimentsmentioning
confidence: 99%
“…Even in summer, soil temperatures in temperate regions are typically lower than those used in our laboratory study. For example, meteorological records at Rothamsted (51.82°N, 0.37°W; Perryman et al , ) indicate that summer soil temperatures at 0.1 m depth normally fall in the range 15–20 °C. We therefore anticipate that the additional power demands of brood incubation under field‐realistic ground temperature conditions may require the thermogenic activity of a greater number of workers than in our warm laboratory environment (Vogt, ).…”
Section: Discussionmentioning
confidence: 99%